PTSD as a mediator of the relationship between trauma and psychotic experiences. Issue 13 (14th October 2022) - Strelchuk, Daniela; Hammerton, Gemma; Wiles, Nicola; Croft, Jazz; Turner, Katrina; Heron, Jonathan; Zammit, Stanley
Abstract: Background: Traumatic experiences are associated with a higher risk of psychotic illnesses, but little is known about potentially modifiable mechanisms underlying this relationship. This study aims to examine whether post-traumatic stress disorder (PTSD) symptoms mediate the relationship between trauma and psychotic experiences (PEs). Methods: We used data from the Avon Longitudinal Study of Parents and Children to examine whether: PTSD symptoms mediate the relationships between (a) childhood trauma and adolescent PEs (study of adolescent PEs; n = 2952), and (b) childhood/adolescent trauma and PEs in early adulthood (study of adult PEs; n = 2492). We examined associations between variables using logistic regression, and mediation using the parametric g-computation formula. Results: Exposure to trauma was associated with increased odds of PEs (adolescent PEs: ORadjusted 1.48, 95% CI 1.23–1.78; adult PEs: ORadjusted 1.57, 95% CI 1.25–1.98) and PTSD symptoms (adolescent PTSD: ORadjusted 1.59, 95% CI 1.31–1.93; adult PTSD: ORadjusted 1.50, 95% CI 1.36–1.65). The association between PTSD symptoms and PE was stronger in adolescence (ORadjusted 4.63, 95% CI 2.34–9.17) than in adulthood (ORadjusted 1.62, 95% CI 0.80–3.25). There was some evidence that PTSD symptoms mediated the relationship between childhood trauma and adolescent PEs (proportion mediated 14%), though evidence of mediation was weaker for adult PEs (proportion mediated 8%). Conclusions: These findings are consistent with the hypothesis that PTSD symptoms partly mediate the association between trauma exposure and PEs. Targeting PTSD symptoms might help prevent the onset of psychotic outcomes.